SSR fingerprinting of 203 sweetpotato (Ipomoea batatas (L.) Lam.) varieties - Yu-sha MENG; Ning ZHAO; Hui LI; Hong ZHAI; Shao-zhen HE; Qing-chang LIU (Journal of Integrative Agriculture)
Simple sequence repeat (SSR) markers have been shown to be a powerful tool for varieties identification in plants. However, SSR fingerprinting of sweetpotato varieties has been a little reported. In this study, a total of 1294 SSR primer pairs, including 1215 genomic-SSR and 79 expressed sequence tag (EST)-SSR primer pairs, were screened with sweetpotato varieties Zhengshu 20 and Luoxushu 8 and their 2 F1 individuals randomly sampled, and 273 and 38 of them generated polymorphic bands, respectively. Four genomic-SSR and 3 EST-SSR primer pairs, which showed good polymorphism, were selected to amplify 203 sweetpotato varieties and gave a total of 172 bands, 85 (49.42%) of which were polymorphic. All of the 203 sweetpotato varieties showed unique fingerprint patterns, indicating the utility of SSR markers in variety identification of this crop. Polymorphism information content (PIC) ranged from 0.5824 to 0.9322 with an average of 0.8176. SSR-based genetic distances varied from 0.0118 to 0.6353 with an average of 0.3100 among these varieties. Thus, these sweetpotato varieties exhibited high levels of genetic similarity and had distinct fingerprint profiles. The SSR fingerprints of the 203 sweetpotato varieties have been successfully constructed. The highly polymorphic SSR primer pairs developed in this study have the potential to be used as core primer pairs for variety identification, genetic diversity assessment and linkage map construction in sweetpotato and other plants.